What are the drivers of tax complexity for multinational corporations? Evidence from 108 countries - Thomas Hoppe; Deborah Schanz; Susann Sturm; Caren Sureth-Sloane (Arbeitskreis Quantitative Steuerlehre (arqus), 2017)
All over the world, firms and governments are increasingly concerned about the rise in tax complexity. To manage it and develop effective simplification measures, detailed information on the current drivers of complexity is required. However, research on this topic is scarce. This is surprising as the latest developments - for example, triggered by the BEPS project - give rise to the conjecture that complexity drivers may have changed, thus questioning the findings of prior studies. In this paper, we shed light on this issue and provide a global picture of the current drivers of tax complexity that multinational corporations face based on a survey of 221 highly experienced tax practitioners from 108 countries. Our results show that prior complexity drivers of the tax code are still relevant, with details and changes of tax regulations being the two most influential complexity drivers. We also find evidence for new relevant complexity drivers emerging from different areas of the tax framework, such as inconsistent decisions among tax officers (tax audits) or retroactively applied tax law amendments (tax enactment). Based on the responses of the practitioners, we develop a concept of tax complexity that distinguishes two pillars, tax code and tax framework complexity, and illustrates the various aspects that should be considered when assessing the complexity of a country's tax system.
Keywords: H20; H25; C83; O57; 330; Complexity Drivers; International Comparison; Survey; Tax Complexity; Tax Practitioners